Characterization of regional differences in cerebral vascular response to breath holding using BOLD fMRI. Issue 1 (29th August 2020) - Chen, Chun‐Ming; Yang, Hui‐Chieh; Hsieh, Hsin‐Hua; Liao, Tsai‐Ying; Huang, Yen‐Chih; Peng, Shin‐Lei
Abstract: Cerebrovascular reactivity (CVR) is a specific indicator of autoregulatory efficiency. Studies have demonstrated that CVR depends on the baseline vascular dilation status between groups. Within the brain, there also exist spatial variations in both the resting cerebral blood flow (CBF) and CVR across different cerebral regions. However, the relationship between the regional CBF and CVR remains unclear. Hence, the primary goal of this study was to investigate the relationship between the resting CBF using pseudocontinuous arterial spin labeling (pCASL) technique and CVR using blood oxygenation level‐dependent (BOLD) technique across different cerebral regions. Eleven male and 14 female young volunteers were recruited in this study. Each subject was asked to perform the breath‐holding challenge to evaluate CVR at 3 T. The resting CBF was measured using pCASL in each subject. The relationships between CBF and CVR across the lobes were evaluated using the Spearman's rank test. The results showed that, for both sexes, the frontal lobe had the maximal resting perfusion but minimal vascular response to hypercapnia, whereas the occipital lobe had the lowest baseline CBF but maximal reactivity to hypercapnia, suggesting low and high autoregulatory efficiencies at high and low resting CBF in the brain, respectively. Sex‐related differences were observed in CBF but not in CVR. These findings may be of clinical interest in the assessment of cerebrovascular reserve and regional‐dependent vascular diseases.